2022
DOI: 10.1021/acsami.2c00155
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility to Improve the Stability of Lithium-Rich Layered Oxides by Surface Doping

Abstract: Li-rich layer-structured oxides are considered promising cathode materials for their specific capacities above 250 mAh·g–1. However, the drawbacks such as poor rate performance, fast capacity fading, and the continuous transition metal (TM) migration into the Li layer hinder their commercial applications. To address these issues, surface doping of Ti and Zr was conducted to the Li- and Mn-rich layered oxide (LMR), Li1.2Mn0.54Ni0.13Co0.13O2. The drop of the average discharge potentials of the Ti- and Zr-doped L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The activity of O in the initial charge process was also probed by sXAS. As shown in Supporting Information: Figure S12, a typical feature peak at ~530.8 eV can be observed when LLO and LLO‐1 are charged at 4.8 V, which represents the characteristic peak of the anionic redox reaction of O 49 . To further explore the systematic evolution of lattice oxygen in the initial charge process, the differential O K‐edge spectra of LLO and LLO‐1 are displayed in Figure 4C,D, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The activity of O in the initial charge process was also probed by sXAS. As shown in Supporting Information: Figure S12, a typical feature peak at ~530.8 eV can be observed when LLO and LLO‐1 are charged at 4.8 V, which represents the characteristic peak of the anionic redox reaction of O 49 . To further explore the systematic evolution of lattice oxygen in the initial charge process, the differential O K‐edge spectra of LLO and LLO‐1 are displayed in Figure 4C,D, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Supporting Information: Figure S12, a typical feature peak at ~530.8 eV can be observed when LLO and LLO-1 are charged at 4.8 V, which represents the characteristic peak of the anionic redox reaction of O. 49 To further explore the systematic evolution of lattice oxygen in the initial charge process, the differential O K-edge spectra of LLO and LLO-1 are displayed in Figure 4C,D, respectively. For both materials, the characteristic peak at 530.8 eV in the differential spectrum gradually increases with the increase of cut-off voltage, indicating the gradually increased activity of oxygen anionic redox.…”
Section: Resultsmentioning
confidence: 99%
“…To address the aforementioned issues, various strategies have been applied, such as surface-coating modification, heteroatom doping, preactivation, structure regulation (such as transition-metal elemental gradient design, , defect regulation, , morphology and size control, , etc.). Meanwhile, the structure regulation by different synthesis processes mentioned above is an essential way to improve its intrinsic electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…30−32 It is mainly ascribed to the fact that these expensive cations' substitution in Ni sites enhance the integrated bond dissolution energy of cathodes by dragging the oxygen more tightly. 33 The gallium element located at group IIIA has shown the obvious role on suppressing the unordered transfer of Ni 2+ to the Li + site. Jamil et al found that the appropriate amount of gallium replacement obviously suppressed the H2−H3 phase transformation of Ni-rich LiNi 0.94 Co 0.04 Mn 0.015 O 2 and effectively stabilized the cathode structure during cycling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Doping modification is also widely applied to protect cathodes from undergoing irreversible transformation within the particles . The major structure stability could be improved by introducing the expensive cation for partial substitution of Ni 2+ , such as Zr 4+ , Nb 5+ , and W 6+ . It is mainly ascribed to the fact that these expensive cations’ substitution in Ni sites enhance the integrated bond dissolution energy of cathodes by dragging the oxygen more tightly . The gallium element located at group IIIA has shown the obvious role on suppressing the unordered transfer of Ni 2+ to the Li + site.…”
Section: Introductionmentioning
confidence: 99%